Various Separation Axioms on -Closed Sets - V, Vaishnavy; K, Sivakamasundari (International Journal of Engineering and Technology, 2018)
The idea behind this article is to introduce and study the notions of -compactness, -connectedness and Gi-axioms. These          notions are characterized using various spaces and different types of continuity.